2012
DOI: 10.1007/s00265-012-1330-7
|View full text |Cite
|
Sign up to set email alerts
|

Female philopatry and its social benefits among Bornean orangutans

Abstract: Female philopatry in mammals is generally associated with ecological and sometimes social benefits, and often with dispersal by males. Previous studies on dispersal patterns of orangutans, largely non-gregarious Asian great apes, have yielded conflicting results. Based on 7 years of observational data and mitochondrial and nuclear DNA analyses on fecal samples of 41 adult Bornean orangutans (Pongo pygmaeus wurmbii) from the Tuanan population, we provide both genetic and behavioral evidence for male dispersal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 60 publications
3
101
1
Order By: Relevance
“…We can therefore exclude logging as a general cause for possible island differences in morph ratios. Furthermore we can exclude differences in dispersal between populations of the two islands as recent studies convincingly showed that on both islands males are the dispersing sex, whereas females are philopatric [24,29,60-62]. …”
Section: Discussionmentioning
confidence: 99%
“…We can therefore exclude logging as a general cause for possible island differences in morph ratios. Furthermore we can exclude differences in dispersal between populations of the two islands as recent studies convincingly showed that on both islands males are the dispersing sex, whereas females are philopatric [24,29,60-62]. …”
Section: Discussionmentioning
confidence: 99%
“…; van Noordwijk et al . ). The third model (IM2‐GR) additionally allowed the two populations to change size exponentially after the population split and corresponded largely to the favoured model in the genomic study by Locke et al .…”
Section: Methodsmentioning
confidence: 97%
“…; van Noordwijk et al . ), mitochondrial markers contain information about population split times without the confounding influence of gene flow. In contrast, Y‐chromosomal loci should have more power than autosomal markers to reveal low levels of male‐mediated gene flow.…”
Section: Introductionmentioning
confidence: 99%
“…exist in a semi-solitary society with roving promiscuity (van Schaik and van Hooff 1996), in which the relatively smaller, philopatric home ranges of females are enveloped by those of dispersing adult males (Galdikas 1985a;van Noordwijk et al 2012). Such males exhibit bimaturism, expressing one of two morphological forms (Fig.…”
Section: Introductionmentioning
confidence: 98%